Classification Of Work on White Cement in The Production of Marble Quarry Waste and Barium Products Based White Cement - Ziyodullayeva Madina Ilhomovna (Zien Journals, 2021)
Production of barrier products based on marble quarry waste and white cement. Accelerate the production of a product using waste marble and save the amount of expensive raw materials, proposing to extend the service life of the product. The use of waste from the processing of marble as a filler and maximum savings on filler consumption. The durability of the product and the mechanism of formation of the structure are theoretically justified.
Keywords: Marble; waste; bardiyar; filler